Publish or Perish? The Steep, Steep Path for Central Asia Journalism and Mass Communication Faculty. (June 2021) - Kurambayev, Bahtiyar; Freedman, Eric
Journalism and mass communication faculty in Central Asian countries face increased institution and government pressure to produce research that appears in Scopus-indexed publications. This study interviews faculty members in Kazakhstan and Kyrgyzstan to examine how they attempt to meet these publication requirements. The findings suggest a disturbing research environment where some faculty resort to unethical means, such as buying and selling research co-authorship or paying to publish in predatory and fake journals.